How to Achieve Profit Growth by Optimizing Operational Resources Based on Total Efficiency in Food and Beverage Companies in Indonesia (International Journal of Scientific Research and Management (IJSRM), 2023)
This study aims to analyze resource optimization on the basis of total efficiency in achieving profit growth in manufacturing companies in Indonesia. Detailed investigations are empirically focused on external financing strategies and the effectiveness of asset management oriented on the basis of total efficiency to achieve profit growth. This study uses a quantitative approach to the explanation of intermediation regression. With a total sample of 12 manufacturing companies in the national food and beverage sector for five years. Financial data analysis methods include descriptive analysis and inferential analysis. The results of this study indicate that Profit Growth can only be significantly affected by Total Efficiency. Leverage is not able to significantly influence Total Efficiency, while Asset Management is able to significantly influence Total Efficiency. Intervening variable Total Efficiency is not able to mediate the relationship between Leverage on Profit Growth and Asset Management on Profit Growth.